Earth’s Temperature Versus the Sun, Water Vapor and CO2 - Lightfoot, H. Douglas (Journal of Basic & Applied Sciences, 2021)
The IPCC report Climate Change 2013: The Physical Science Basis (AR5) has two opposing claims as causes for an increase in the Earth’s temperature in the decades leading up to 2011. In one claim, the cause is an increase in the level of CO2 in the atmosphere. In the second claim, it is an increase in water vapor measured as specific humidity. The purpose of this study is to determine which claim is correct. Several published studies are brought together to form a coherent picture of the interaction between the Sun, water vapor, and the non-condensing greenhouse gases (GHGs), such as carbon dioxide, methane, and nitrous oxide. Back radiation is the sum of radiation back to the Earth from all GHGs. Warming by water vapor measured as specific humidity is approximately 85.5% to 96.5% of the warming by back radiation. The Sun controls Earth’s temperature through specific humidity. The relationship between air temperature and specific humidity is presented in terms of numerical values. Thus, the portion of a temperature caused by specific humidity can be readily estimated.